Discharge Transition Experience for Lumbar Fusion Patients: A Qualitative Study. Issue 6 (6th December 2021) - Kim, Jeoung Hee; Shin, Yong Soon
ABSTRACT: BACKGROUND: Support should be provided to individuals who are ready to be discharged; however, quantitative research is lacking in understanding the challenges of postsurgery lumbar fusion patients' discharge and transition. This article delves into the in-depth experience of lumbar fusion patients with discharge transitions. METHODS: We conducted semistructured individual interviews with 11 patients who had lumbar fusion surgery at one of Korea's most equipped general hospitals. These interviews focused on the patients' discharge transition experiences. The data were analyzed using phenomenological analysis. RESULTS: Lumbar fusion patients' experiences of discharge transition fit into 4 categories: anticipation of surgical transition, the process of transition to discharge, the difficult process of recovery, and recovery strategy. CONCLUSION: To further expedite the discharge process and make better use of cooperative hospital resources, conducting preoperative treatment planning, identifying family and social support systems, and sharing treatment procedures are all required. Furthermore, thorough health information services and step-by-step courses on predicted problems and everyday living after surgery should be considered for postoperative education. It is critical to broadening the scope of preoperative and postoperative education programs, as well as assistance for the social support system, such as the family-based support system and cooperative hospitals.